Teacher Development and Management : Overview of Policy Briefs - Allemano, Eric; Baumgart, Neil; Chapman, David; Craig, Helen; Kraft, Richard; Rawlinson, Ralph; Thornton, Hilary (World Bank, Washington, DC, 2014)
This is an overview of policy briefs on continuous professional development of teachers, from the ealiest years onward.Studies focussed on the early years are: Effective Teachers and Performance Standards, which looks at how formal qualifications of teachers, and other information frequently recorded on a database of teachers, seldom predict effectiveness in raising student achievement. Accreditation of teacher education institutions and programs; Teacher Certification; Teacher Educators and Initial Teacher Education Programs; Teacher Recruitment and Deployment (paper forthcoming). Papers focussed on the years after the initial training are: Induction Programs for Newly Trained Teachers; Continuous Professional Development (CPD); Teacher Support Networks; Teacher Motivation: Incentives and Working Conditions; Teacher Supervision and Monitoring (paper forthcoming); Teacher Collaboration (paper forthcoming); Professional Development Frameworks (paper forthcoming); Role of Unions/Professional Associations to Support Teachers (paper forthcoming). Additonal topics are: HIV and AIDS and Teachers, and Specific Skill Development including use of technology and multi-grade instruction (papers forthcoming).